Prescribing in schizophrenia and psychosis: Increasing polypharmacy over time. (March 2017) - Heald, Adrian; Livingston, Mark; Yung, Alison; De Hert, M.A.
Abstract: Introduction: Diabetes, obesity, and metabolic syndrome are highly prevalent in patients with severe mental illness. Psychotropic polypharmacy is becoming increasingly prevalent within the UK. We determined the change in the number of psychotropic medications prescribed over time and trends in weight and fasting blood glucose. Methods: One hundred ninety‐five individuals with schizophrenia and psychosis on the Severe Mental Illness Register in Cheshire, UK, were followed up between 2004 and 2012. Individuals were identified through a semianonymised search of general practitioner registers. Results: The total number of different medications prescribed increased from 140 in 2004 to 226 in 2012 with the mean number of medication groups per patient increasing from 0.71 to 1.15 ( p < .001). The number of individuals on no medication reduced from 58.0% to 33.3%, OR 0.36 95% CI [0.24, 0.54], and those prescribed one medication increased from 20.5% to 31.8%, OR 1.93 95% CI [1.22–3.06]. Baseline body mass index was 28.9, increasing to 30.8 at 8‐year follow‐up, F (6.5), p = .003, with a significant corresponding increase in fasting blood glucose. Conclusion: In conclusion, we determined an increase in psychotropic polypharmacy over the follow‐up period. Body mass index or fasting blood glucose increased over time. Clozapine and depot antipsychotic prescriptions were often not recorded in the general practitioner records.